Interface stress evolution considering the combined creep–plastic behavior in thermal barrier coatings. (5th January 2016) - Chen, Lin; Yueming, Li
Abstract: In this paper, the interface stress evolution in thermal barrier coatings (TBC) is numerically investigated by considering the combined creep–plastic behaviors of thermally grown oxide (TGO) and bond-coat (BC). The return-mapping type algorithm is proposed for the solution of combined creep–plastic constitutive model. The diffusion oxidation-reaction scheme is introduced to describe TGO growth. The numerical results reveal that the TGO creep leads to the relaxation of stress in both top-coat (TC) and BC layers, and the BC creep decreases the stress in BC layer but increases the stress in TC layer, as well as the plastic deformation affects the stress evolution too but its influence is insignificant during oxidation. On cooling, the plasticity rather than the creep affects stress evolution, and the strength properties can affect not only the magnitude but the location of maximum interface stress. Graphical abstract: Highlights: Combined creep–plastic model is proposed to characterize TBC mechanical properties. Return-mapping type algorithm is developed to solve combined creep–plastic model. Diffusion oxidation-reaction scheme is introduced to describe TGO growth. Influence of mechanical properties on interface stress evolution is investigated.